Hypertension Prevalence, Awareness, Treatment, and Control and Sodium Intake in Shandong Province, China: Baseline Results From Shandong–Ministry of Health Action on Salt Reduction and Hypertension (SMASH), 2011 - Bi, Zhenqiang (Centers for Disease Control and Prevention, 2014)
INTRODUCTION: In China, population-based blood pressure levels and prevalence of hypertension are increasing. Meanwhile, sodium intake, a major risk factor for hypertension, is high. In 2011, to develop intervention priorities for a salt reduction and hypertension control project in Shandong Province (population 96 million), a cross-sectional survey was conducted to collect information on sodium intake and hypertension prevalence, awareness, treatment, and control. METHODS: Complex, multistage sampling methods were used to select a provincial-representative adult sample. Blood pressure was measured and a survey conducted among all participants; condiments were weighed in the household, a 24-hour dietary recall was conducted, and urine was collected. Hypertension was determined by blood pressure measured on a single occasion and self-reported use of antihypertension medications. RESULTS: Overall, 23.4% (95% confidence interval [CI], 20.9%–26.0%) of adults in Shandong were estimated to have hypertension. Among those classified as having hypertension, approximately one-third (34.5%) reported having hypertension, approximately one-fourth (27.5%) reported taking medications, and one-seventh (14.9%) had their blood pressure controlled (<140/<90 mm Hg). Estimated total average daily dietary sodium intake was 5,745 mg (95% CI, 5,428 mg–6,063 mg). Most dietary sodium (80.8%) came from salt and high-salt condiments added during cooking: a sodium intake of 4,640 mg (95% CI, 4,360 mg–4,920 mg). The average daily urinary sodium excretion was 5,398 mg (95% CI, 5,112 mg–5,683 mg). CONCLUSION: Hypertension and excessive sodium intake in adults are major public health problems in Shandong Province, China.